Effectiveness of Hosyo essential oil concerning autonomic nervous function - TANAKA, Atsushi; YOSHIMOTO, Ryuji; TENMA, Kazuto (Japan Journal of Aromatherapy, 2021)
[Introduction] The symbolic tree of Kagoshima Prefecture is a camphor tree. Historically, camphor was produced from camphor tree at the Satsuma Domain in Edo period. Even today, the rare natural essential oil in the world from Hosyo, a kind of camphor tree, is produced by Kaimon district at Ibusuki city in Kagoshima Prefecture. L-linalool, one of the main lavender essential oil ingredients having a sedative effect, is the main ingredient of the Hosyo essential oil. Various previous studies have shown that aromatherapy with lavender essential oil has a relaxing effect. The study aims to investigate the effect of the essential oil from Hosyo on the autonomic nervous system by pulse wave. [Methods] Seventeen healthy young females attended the study and were in the sitting position on a chair. In this study, every subject underwent a 5-minute rest, 5-minute aromatherapy, and 10-minute post aromatherapy in correct order. Simultaneously, pulse wave is gained from the fingertip pulse wave meter. The subjects smelled a drop (0.05 mL) of Hosyo essential oil on the tissue paper. Five fingertip pulse wave parameters (HF, LF/HF, pulse, CVRR, entropy) were calculated and analyzed using TAOS company product. HF is the indicator of parasympathetic nervous system activation; LF/HF is the sympathetic nervous system indicator. Before and after the study, fatigue using VAS, Japanese Society of Fatigue Science evaluation form, and the likes and dislikes of Hosyo essential oil are assessed. Questionnaires to fragrance were also distributed and answered. [Results] Aromatherapy has a meaningful increase in HF and decrease in LF/HF compared that of the rest. Pulse wave showed gradually decrease during aromatherapy. Fatigue with VAS was meaningfully improved. [Conclusion] Only the 5-minute aromatherapy with Hosyo essential oil activated and inhibited the parasympathetic and sympathetic nervous system, respectively. This aromatherapy shows immediate effect.